THE ARABIC LANGUAGE AND ITS URGENCY IN UNDERSTANDING THE QUR'AN - Choli, Ifham; Mujib, Ahmad (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2026)
Arabic plays a crucial role in understanding and interpreting the Qur'an. Arabic is the language of the Qur'an, and there is a correlation between it and Qur'anic interpretation. This literature review aims to examine Arabic and its importance in understanding the Qur'an, a subject of increasing public interest. The study's findings demonstrate that Arabic plays a fundamental role in understanding the full meaning of the Qur'an. The root-based structure of Arabic (jidzr al-kalimah) allows a single word to contain multiple, interrelated meanings. Differences in word form, pattern (wazan), and pronunciation can produce significant differences in meaning. Therefore, understanding Arabic is a key prerequisite for accurately interpreting Qur'anic verses. In the science of exegesis, Arabic plays a crucial role, including understanding the semantic meaning of Qur'anic verses and understanding their intended meaning. Translations of the Qur'an cannot replace the Arabic text as the primary source of Islamic law and teachings. Thus, mastery of Arabic is an urgent need, especially for students who want to understand the Qur'an in depth and contextually.